Assessing quality of life among elementary school students: Validation of the Korean version of the Meaning in Life in Children Questionnaire - Choi, Younyoung; Shin, Joo Yeon (Frontiers in Psychology, 2022)
Meaning in life (MIL) has been widely recognized as a hallmark of psychological well-being and positive youth development. The goal of this study was to validate the Korean version of the Meaning in Life in Children Questionnaire (K-MIL-CQ) utilizing the framework suggested by the Standards for Educational and Psychological Testing. Data were obtained from 277 fifth graders aged 10–11 in three elementary schools in Seoul and Gyeonggi through a paper-and-pencil survey (55.2% boys). We translated the MIL-CQ, a 21-item self-report measure developed based on Frankl’s “meaning triangle,” into Korean. Psychological well-being measures were also assessed. Validity and reliability data were collected. (1) The content of domains and items was appropriate for measuring MIL among children. (2) A three-factor model consisting of attitude, creativity, and experience pathways was extracted via exploratory factor analysis, and a three-factor hierarchical model including attitude, creativity, and experience as first-order factors and MIL as a second-order factor was confirmed via confirmatory factor analysis. (3) Higher levels of MIL were related to higher levels of satisfaction with life, self-esteem, positive affectivity, and lower levels of negative affectivity. (4) All item fit statistics were acceptable based on the Rasch model. (5) The analysis of the measurement invariance of each item showed that the responses to one item varied by gender, suggesting that additional items might facilitate better measurement of MIL in children. This study provides validity and reliability evidence that K-MIL-CQ is appropriate for measuring MIL among South Korean elementary school students.